Shades of Love in Love in The Time of Cholera - Castelli, Alberto (Verbum – Analecta Neolatina, 2024)
As lovers, we pretend perfect symmetry; the language of love is, however, essentially asymmetrical. Roland Barthes’ A Lover’s Discourse (1977) is a philosophical exploration of a lover’s inner monologue in which the chaotic flux of emotions that spring from a lover’s mind create the asymmetrical space of possibility. García Márquez’s Love in The Time of Cholera is the tale of a melancholy passion that never rises into oblivion. Florentino Ariza, the protagonist who suffers without adjustment, reenacts in fiction Barthes’s psychological mediation. By confronting his relation with time, in terms of eternity rather than future, and by encountering love with wait rather than possession, Florentino, transforms the classical Liebestod into a cathartic and transcendental experience.